The Constraints of women refugees in accessing work: the case of Syrian refugees in Lebanon - Zoubi, Saja al (International Center for Agricultural Research in the Dry Areas, 2017)
This presentation was supposed to be given by Saja al Zoubi (ICARDA), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.